Estilos de aprendizaje: pautas metodológicas para trabajar en el aula - Martínez Geijo, Pedro (Revista Complutense de Educación, 2008)
Learning styles can be implemented according to the two teaching approaches that coexist in today’s classrooms, namely, the transmissive and the constructivist. When methodology is considered within the framework of the transmissive approach, awareness of learning styles becomes an added task to every day classroom practice. However if teaching is carried out in accordance with the constructivist focus, then attention to learning styles is integrated into the teacher’s daily work. Both standpoints propose methodological guidelines which help promote attention to the students’ diversity.